Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1084/jem.179.5.1689
|View full text |Cite
|
Sign up to set email alerts
|

Production of the RANTES chemokine in delayed-type hypersensitivity reactions: involvement of macrophages and endothelial cells.

Abstract: SummaryTo understand the selective accumulation of memory T helper lymphocytes and of macrophages in delayed-type hypersensitivity (DTH) granulomas, we studied the in situ production of RANTES, a chemokine initially characterized on the basis of its in vitro chemotactic properties for each of these cell populations. RANTES gene expression was studied by in situ hybridization in 15 human lymph nodes presenting typical DTH lesions related to either sarcoidosis or tuberculosis. A positive signal was detected in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(119 citation statements)
references
References 34 publications
8
108
2
1
Order By: Relevance
“…Only a few studies have examined the induction of genes for MCP-3, MIP-1b and I-309 (TCA3) in diseased states, but MIP-1a and RANTES have been shown to be involved in several diseases [26][27][28][29][30][31][32][33][34][35]. In glomerular diseases, Tang et al [23] demonstrated that expression of genes for MCP-1 and MIP-1a, but not for RANTES, was enhanced in a non-crescentic anti-GBM model.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the induction of genes for MCP-3, MIP-1b and I-309 (TCA3) in diseased states, but MIP-1a and RANTES have been shown to be involved in several diseases [26][27][28][29][30][31][32][33][34][35]. In glomerular diseases, Tang et al [23] demonstrated that expression of genes for MCP-1 and MIP-1a, but not for RANTES, was enhanced in a non-crescentic anti-GBM model.…”
Section: Discussionmentioning
confidence: 99%
“…RANTES has been shown to play a role in DTH responses, but would normally be considered pro-inflammatory (Devergne et al 1994). The reduction in local levels of RANTES in response to OVX (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…17 Chemokines are a large family of soluble molecules expressed by ECs, smooth muscle cells, or lymphocytes that attract, and in many cases activate, a variety of inflammatory and noninflammatory cells. 18,19 Chronic allograft endothelial injury leads to macrophage migration, as well as the eventual accumulation and proliferation of intimal smooth muscle-like cells. 19 -21 To date, more than 50 chemokines have been identified.…”
Section: Discussionmentioning
confidence: 99%